Weather : air masses, clouds, rainfall, storms, weather maps, climate - Lehr, Paul E.; Burnett, R. Will (Raymond Will), 1912-; Zim, Herbert S. (Herbert Spencer), 1909-1994; McNaught, Harry (New York : St. Martin's Press, 1993)
An illustrated guide to the atmospheric causes and major phenomena of weather including instruments used to forecast and plot it.
Originally published: New York : Golden Press ; Racine, Wis. : Western Pub. Co., 1987.
Includes bibliographical references (p. 157) and index.
Keywords: Meteorology; Weather